The entrepreneurial earnings puzzle. Evidence from matched person-firm data - Arvid Raknerud; Mirjam van Praag (Statistics Norway, Research Department, 2014)
Empirical studies show that the pecuniary returns to an individual's decision to switch from wage employment to entrepreneurship are low. We reconsider the pecuniary gains from this transition using a unified and flexible approach based on a mixed model with heterogeneous returns to entrepreneurship. Addressing the issue of self-selection, we analyze to what extent earlier findings are obscured by mixing individuals who become entrepreneurs without interesting wage alternatives with those who do have a realistic alternative opportunity. Our data set covers the whole Norwegian population of individuals matched to the entire population of firms established in the period 2002– 2011, and includes extensive income and ownership share measures. The results indicate that the average return to entrepreneurship is significantly negative for individuals entering entrepreneurship through self-employment. Entrepreneurs who establish firms by injecting the minimum (or close to minimum) required amount of equity in an incorporated firm at start-up, have a significantly positive, but low return to entrepreneurship on average. Finally, persons who become entrepreneurs by establishing firms that are at least twice as large as the minimum requirement, increase their earnings by 10 percent on average by becoming entrepreneurs. We identify a significant positive selection by absolute advantage with regard to the choice of becoming an incorporated entrepreneur, but not with regard to self-employment.
Keywords: L26; C23; J31; 330; Entrepreneurship; Returns to entrepreneurship; Earnings distribution; Matched personfirm data